Studenci a Praska Wiosna - Kobus, Andrzej (Acta Universitatis Lodziensis. Folia Historica, 2001)
The article contains the description of Czechoslovakian academic circles between October 1967 and the Beginning of 1969. The introduction presents the students circles’ situation in 1960s (before 1967), especially all forms of resistance and political activities against the communist regime. The events of Strachovo in October 1967 (demonstrations in students district in Prague) are showed in further part of the article. The enthusiasm of students was visible because of the new authority’s reforms of spring 1968. The independent organization of Czech and Moravian students appeared. The article shows the reactions against the August intervention of the Warsaw Pact as well. The further part of the article gives the picture of students’ attitude towards the new, occupation reality of Czechoslovakia (strikes in November 1968 and tragic suicides of Jan Palach and Jan Zojic in the beginning of 1969). At the end of article the process of so called „normalisation" is described (starting from April 1969). That means leaving the social-political postulates of the „Prague spring” and repressions in 1969 and 1970 against the supporters of Dubček’s group. Conclusion covers the role and sense of events that look place in Czechoslovakia between 1967 and 1969.